2010
DOI: 10.1038/onc.2010.509
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin regulates EMT induction by Slug and oncogenic H-Ras and migration by governing Axl expression in breast cancer

Abstract: Epithelial-to-mesenchymal transition (EMT) is a critical event in the progression toward cancer metastasis. The intermediate filament protein vimentin is an important marker of EMT and a requisite regulator of mesenchymal cell migration. However, it is not known how vimentin functionally contributes to cancer cell invasion. Here, we report that ectopic expression of oncogenic H-Ras-V12G and Slug induces vimentin expression and migration in pre-malignant breast epithelial cells. Conversely, vimentin expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
462
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(521 citation statements)
references
References 53 publications
43
462
1
6
Order By: Relevance
“…Recent studies showed that vimentin also contributes functionally to EMT phenotypes including cell migration and invasion. This suggests that ILK plays a critical role in directly regulating EMT signals, as well as mediating EMT signals to reorganization of the cytoskeleton in RCC cells (36,37). Our data show that vimentin expression is regulated by ILK expression, which suggests that ILK regulates the EMT in RCC in various ways.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Recent studies showed that vimentin also contributes functionally to EMT phenotypes including cell migration and invasion. This suggests that ILK plays a critical role in directly regulating EMT signals, as well as mediating EMT signals to reorganization of the cytoskeleton in RCC cells (36,37). Our data show that vimentin expression is regulated by ILK expression, which suggests that ILK regulates the EMT in RCC in various ways.…”
Section: Discussionmentioning
confidence: 59%
“…ILK silencing inhibited PARP-1 binding to SIRE, and PARP-1 silencing decreased both Zeb1 and Snail, which resulted in the upregulation of E-cadherin (35). Vimentin, the intermediate filament protein, is an important marker of the EMT and a requisite regulator of mesenchymal cell migration (36). Recent studies showed that vimentin also contributes functionally to EMT phenotypes including cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a similar role for ZNF652 as a suppressor of breast cancer cell invasion. We demonstrate that ZNF652 directly represses TGFB1, TGFB2, TGFBR2, EGFR, SMAD2 and VIM; genes that have all been previously implicated in the promotion of mesenchymal transformation and invasion (6,(31)(32)(33)(34). As such, we have defined a new role for ZNF652 as a master regulator of the EMT gene network.…”
Section: Targets Of the Mutant P53 • Mir-155 Axismentioning
confidence: 60%
“…An increased expression of the intermediate filament vimentin is another indication of mesenchymal acquisition during EMT (Morabito et al, 2001;Vuoriluoto et al, 2011). The defect in mesenchymal gene expression is further demonstrated in the B WT-1 /B WT-1 compact myocardium in vivo as evaluated by vimentin expression.…”
Section: Nmiib Is Required For Mesenchymal Maturation During Epicardimentioning
confidence: 90%